Fine-Root Traits Reveal Contrasting Ecological Strategies in European Beech and Norway Spruce During Extreme Drought - Nikolova, Petia Simeonova; Bauerle, Taryn L.; Häberle, Karl-Heinz; Blaschke, Helmut; Brunner, Ivano; Matyssek, Rainer (Frontiers in Plant Science, 2020)
Trees adjust multiple structural and functional organ-specific characteristics, ‘traits‘, to cope with diverse soil conditions. Studies on traits are widely used to uncover ecological species adaptability to varying environments. However, fine-root traits are rarely studied for methodological reasons. We analyzed the adaptability of the fine-root systems of European beech and Norway spruce to extreme drought within species-specific tree groups at Kranzberger Forst (Germany), focusing on the seasonality of morphological, physiological and biochemical key traits in view of carbon and nitrogen dynamics. We hypothesized that fine roots of both species adjust to seasonal drought: with beech representing a ‘fast’ (i.e. with fast carbon (C) turnover), and spruce a ‘slow’ (i.e. with long-term C retention) ecological strategy. We identified three functional fine-root categories, based on root function (absorptive or transport fine roots), and mycorrhizal status of the absorptive fine-roots (mycorrhizal or non-mycorrhizal). Solely the non-mycorrhizal absorptive roots adjusted in a species-specific manner supporting fine-root ecological strategy hypothesis. During drought, beech produced thin ephemeral (absorptive non-mycorrhizal) fine roots with high specific fine-root area and high respiratory activity, representing fast C turnover and enabling effective resource exploitation. These adjustments reflect a ‘fast’ ecological strategy. Conversely, spruce absorptive fine roots did not respond to the soil moisture deficit by growth but instead increased root suberization. Drastically lowered respiratory activity of this functional category facilitated C retention and structural persistence during drought, indicating a ‘slow’ ecological strategy in spruce. Absorptive mycorrhizal fine roots maintained respiration throughout the drought event in both tree species, but in spruce this was the only fine-root category with high respiration. This suggests, that spruce relies heavily on mycorrhizal associations as a method of drought resistance. Accumulation of non-structural carbohydrates and high C concentrations were observed in the transport fine roots of both species, indicating drought-induced osmotic protection of these roots. Thus, functional classification enabled us to determine that fine-root branches of each species are not tied to one sole ecological strategy. The suggested approach helps to better understand the complex interplay between structure and function belowground.